Investigation of treatment motivation in alcohol-dependent patients followed by a recovery model: a controlled study - Savaşan, Ayşegül; Çam, Olcay (Journal of Dependence, 2016)
Objective: The aim of this study is to determine the effect of the psychiatric nursing approach based on the Tidal Model on motivation for treatment in alcohol-dependent patients.Method: A quasi experimental pretest post-test research design with control group was conducted with 36 individuals (18 experimental, 18 control). As a measurement instrument, the Treatment Motivation Questionnaire (TMQ), The Addiction Profile Index (BAPI), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) were used. The measures were applied before the application and after the three months of the application.Results: At the end of the three month follow up, alcohol use by individuals in the experimental group was found to be less than that of the control group; individuals in the experimental group who was at the maintenance stage were found to be more than the control group; and the craving score decreased in the experimental group, but increased in the control group. It was found that internal and external motivation, interpersonalhelp-seeking and total motivation of the experimental group decreased or remained the same and confidence-in-treatment of them increased at the end of three months; however the difference was not significant. Internal motivation in the control group was significantly reduced. However, when compared with the experimental group, the difference in change between the two groups was found not to be significant.Conclusion: The psychiatric nursing approach based on the Tidal Model may have prevented a significant reduction in especially internal motivation of the experimental group. It is recommended that follow-up studies should be conducted to prevent the relapse and randomized controlled studies should be conducted with regard to the most frequently seen problems of alcohol-dependent individuals.
Keywords: Alcohol dependence; Motivation for treatment; The Tidal Model